Outcome of infants with bronchopulmonary dysplasia - Dwi Kisworo Setyowireni; Roni Naning; Rina Triasih; Indah Kartika Murni; Madarina Julia; Ekawaty Luthfia Haksari (PLoS ONE, 2025)
Background Bronchopulmonary dysplasia (BDP) is the most common chronic lung disease in infants. The study aimed to evaluate the outcome of infants diagnosed with BPD in Yogyakarta, Indonesia. Material and methods A retrospective cohort study was conducted by reviewing the medical records of infants with BPD born between January 2015 and December 2020 at Dr. Sardjito General Hospital in Yogyakarta, Indonesia. Surviving children were invited for clinical assessment and echocardiogram. A multivariate logistic regression analysis was used to identify predictors of mortality. Results Among 8,490 newborns hospitalized in the Perinatal ward, 100 (1.2%) developed BPD, with neonatal sepsis and congenital heart disease as the most prevalent comorbidities. Of the 85 infants with complete data, 41 (48.2%) died within 7 months. Multivariate analysis revealed that post-menstrual age (PMA) < 28 weeks and mechanical ventilation as independent predictors of mortality, with adjusted odds ratios (ORs) (95% CI) of 5.27 (1.36-20.43) and 0.26 (0.09-0.75), respectively. Conclusions Nearly half of the infants diagnosed with BPD died within the first seven months of life. PMA < 28 weeks was associated with increased mortality risk, while mechanical ventilation showed a protective effect against mortality in infants with BPD.